Different Effect of Lanthanum Carbonate and Sevelamer Hydrochloride on Calcium Balance in Patients with Moderate to Advanced Chronic Kidney Disease - Makowka A; Nowicki M (Dove Medical Press, 2021)
Agnieszka Makowka, Michal Nowicki Department of Nephrology, Hypertension and Kidney Transplantation, Medical University of Lodz, Lodz, PolandCorrespondence: Michal NowickiDepartment of Nephrology, Hypertension and Kidney Transplantation, Medical University of Lodz, Central University Hospital, Pomorska Str 251, Lodz, 92-213, PolandTel +48 42 2014400Fax +48 42 2014401Email nefro@wp.plObjective: Opposite to lanthanum carbonate (LC), sevelamer hydrochloride (SH) may increase intestinal calcium absorption. The study compared the effects of LC and SH on serum and urine phosphate and calcium, and on hormones regulating mineral-bone metabolism.Patients and Methods: A prospective randomized crossover study included 34 patients with eGFR < 60 mL/min. A single oral dose of LC (1,000 mg) or SH (2,400 mg) was administered in random order 15 minutes after a standardized meal fortified with 5 g calcium carbonate. Serum calcium, phosphate, and parathormone were measured before and 3, 6, 12, and 24 hours after each medication. Bone alkaline phosphatase (BAP), sclerostin, calcitriol, and FGF-23 were measured at baseline and after 12 and 24 hours. A 24-hour calcium and phosphate excretion was measured after each drug.Results: Serum calcium increased 3 and 6 hours after SH then returned to baseline. After LC calcium was unchanged for up to 3 hours then transiently increased and eventually returned to baseline. The area under curve (AUC) of serum calcium for 12 hours after SH was larger than after LC (p=0.04). Serum phosphate decreased after each drug with a nadir 3 hours post-SH and 6 hours post-LC. AUC of serum phosphate was similar after both medications. PTH decreased transiently after both drugs. BAP did not change. FGF-23 was constant for the first 12 hours but later decreased after each drug.Conclusion: A 2,400 mg SH and 1,000 mg LC are similarly effective in lowering serum phosphate in CKD, but LC induce in less intestinal calcium absorption after a meal. The trial was registered on February 23, 2018 in the clinicaltrial.gov database - NCT03451019.Keywords: calcium, chronic kidney disease - mineral bone disorder, hyperphosphatemia, phosphate-binders, PTH